Regulation of Minimum Rates in Transportation - Bigham, Truman C. (Quarterly Journal of Economics, 1947)
Importance of the problem, 206. — Congressional directives, 207. — General attitude of the Commission, 208. — Minimum rates and discrimination, 211. — Adequacy of revenue, 211. — Protection of the rate structure, 214. — Preservation of the advantages of particular modes of transport: the value standard, 220; particular agencies, 223; cost standards, 225. — Conclusions, 229.